Implementación de instrumentos básicos en el área de ciencias naturales y el laboratorio, mediante gestión en instituciones públicas y privadas, para mejorar los procesos educativos en los estudiantes del cuarto año de educación general básica de la escuela “Alejandro Dávalos Calle” del cantón Salcedo en el período 2012-2013 - Cañar Chasi, Aida Marina (2013)
The present work will based in the increase the basic instruments of the science laboratory in the “Alejandro Dávalos Calle” hight school as through the get information of the applied survey to each one of the authorities and students in the theoretical-practical teaching, because at present this institution there aren´t the basic instruments to perform with the pedagogical need. Through the management in public and private institutions, it can to reach the economic support to acquire the basic instruments to a science laboratory; it is just directed to fourth year of Basic General Education.